Reproductive responses of anoestrous indigenous does to male introduction during postpartum* - MONDAL, S K; JOSHI, H C; MAJUMDAR, A C; MAJUMDAR, S; VARSHNEY, V P; DUTT, TRIVENI; PANDEY, H N (The Indian Journal of Animal Sciences, 2011)
The present study was conducted on 18 postpartum anoestrous local does of 3.27±0.38 years of age and 17.54±1.02 kg of body weight to elucidate the male effect. The does, completely isolated from males (average 92 days postpartum), were divided into 3 equal groups – control (D), ram-teased (DR) and buck-teased (DB) and their reproductive responses were recorded to compare the teasing effect by intact, sexually experienced and aproned males. The ‘male effect’ was determined on the basis of the parameters like proportion of females in oestrus, post-exposure interval to behavioural oestrus, oestrus duration, standing heat length and oestrus intensity. Teasing with buck (DB) and ram (DR) induced heat, respectively, in 6/6 and 5/6 postpartum does that were significantly higher than the control (D) does (2/6). When teased with males, the does showed behavioural oestrus within 2.6 (DB), 7.8 (DR) and 23 (D) days of male exposure in teased groups, respectively and subsequently ovulated. The intervals were significantly different among the groups. The oestrus duration, standing heat length and oestrus intensity were significantly affected by the male teasing. The oestrus synchronization in does was 5/6 vs 1/6 within 3 days of introduction of buck and ram, respectively. The duration of oestrus was 21.9 h (DB), 33.2 h (DR) and 47 h (D) while standing heat length was 3.83 h (DB), 6.64 h (DR) and 10 h (D). The oestrus intensity score was recorded to be 4.4 (DB), 3.3 (DR) and 1.5 (D). The incidence of anovulatory oestrus and silent oestrus was not found in the present study. The ovulation was ascertained by the circulating progesterone concentration (first estimation of >0.5 ng/ml of serum after male introduction). The average oestrus to ovulation interval was recorded to be 0.99 (DB), 1.72 (DR) and 2.20 days (D). The occurrence of short cycles in the male-teased groups was not observed. It was concluded that there did exist a significant effect of male introduction in previously isolated flock of postpartum anoestrous local does and this ‘male effect’ may be utilized as a tool for manipulating the reproductive status of indigenous does.